Stance control is not affected by paresis and reflex hyperexcitability: the case of spastic patients. Issue 5 (1st May 2001) - Nardone, A; Galante, M; Lucas, B; Schieppati, M
Abstract : OBJECTIVES: Spastic patients were studied to understand whether stance unsteadiness is associated with changes in the control of voluntary force, muscle tone, or reflex excitability, rather than to abnormal posture connected to the motor deficit itself. METHODS: Twenty four normal subjects, 12 patients affected by amyotrophic lateral sclerosis (ALS), seven by spastic paraparesis, and 14 by hemiparesis were studied. All patients featured various degrees of spasticity and paresis but were free from clinically evident sensory deficits. Body sway during quiet upright stance was assessed through a stabilometric platform under both eyes open (EO) and eyes closed (EC) conditions. The sudden rotation of a supporting platform, in a toe up and toe down direction respectively, evoked short (SLR) and medium latency (MLR) reflex responses to stretch of the soleus or the tibialis anterior (TA) muscle. RESULTS: No relation was found between clinical findings (tone, muscle strength, tendon reflexes, plantar response, and duration of disease) and body sway. On average, all patient groups exhibited a forward shift of the centre of foot pressure (CFP) with respect to normal subjects; in addition, paraparetic and to a much larger extent hemiparetic patients showed a lateral shift of CFP. Body sway area was significantly increased only in the hemiparetic patients. No relation was found between position of the CFP and sway within any patient group. Soleus SLR was increased in all patients with respect to normal subjects. TA SLR was often seen in both patients with ALS and paraparetic patients, but only rarely in normal subjects and hemiparetic patients. However, no relation was found between amplitude of soleus or TA SLRs and stabilometric variables. The frequency and size of soleus MLR and TA MLR were decreased in all patients. These responses were decreased in size and not modulated by background EMG in the affected leg of hemiparetic patients, suggesting a disturbed control of spinal reflexes fed by spindle group II afferent fibres. CONCLUSIONS: It is proposed that body posture, paresis, or monosynaptic reflex hyperexcitability do not affect the control of equilibrium during quiet upright stance. In hemiparetic patients, the decreased amplitude of MLRs might be the main cause of the large postural instability. The results are congruent with the hypothesis of a role for group II afferent input in the reflex control of equilibrium.